Combustion and emission characteristics of natural gas engine with partial-catalytic oxidation of the fuel. (15th March 2022) - Zheng, Jian; Zhou, Rui; Zhan, Reggie; Lin, He
Highlights: The addition of fuel reforming gas simultaneously reduced NOX and HC emissions from natural gas engines. CO emissions showed a trade-off to NOx and HC emission. The addition of fuel reforming gas showed no damage of economic performance of the engine. A promising on-board fuel reforming scheme for vehicles was proposed. Abstract: Combustion, emission characteristics and the economic performance of a heavy-duty natural gas engine blended with different ratios of reformed gas were investigated, and the feasibility of applying the fuel partial oxidation catalytic reforming system on a heavy-duty natural gas engine was discussed. Experimental results showed that the use of Rh/γ-Al2 O3 as a catalyst of partial oxidation reaction of natural gas fuel requires low initial reaction inlet gas temperature, and it has good catalytic performance and durability, which makes it feasible to be applied on vehicles. Blending with reformed gas from partial oxidation reaction significantly reduces NOX and CH4 emission and effectively reduces coefficient of variance of peak pressure. In additions, no significant change in fuel consumption was observed after blending with reformed gas, while CO emissions increased. In general, the combination of on-board fuel partial oxidation catalytic reforming system to improve the performance of natural gas engines has good prospects.